The effects of nano kaolin clay modified bitumen on the softening point and storage stability - Putra Jaya, Ramadhansyah; Z. F., Mohamed Jaafar; K. A., Masri; N., Mashros; M. N., Mohd Warid; A. H., Norhidayah; H., Yaacob (IOP Publishing Ltd, 2021)
Utilisation of nanomaterials in asphalt binder is widely explored to improve the performance of the bitumen. Among the potential of nanomaterials, nanoclay received much attention as a modifier in bitumen modification due to their low cost of production and abundance in nature especially in tropical country. This study focused on investigating the physical properties of bitumen containing nano kaolin clay (NKC). The NKC were added at different percentages (3%, 5%, 7%, and 9%) for the modified bitumen production. The softening point and storage stability test were carried out in order to study the physical properties of bitumen. The results show that the addition of nano kaolin clay positively impacts the physical performance of the asphalt binder. It is enhancing the stiffness in terms of softening and storage stability value.